A prospective study on outcome of dorsal versus ventral buccal mucosal graft urethroplasty for bulbar urethral stricture - Shaik, Jamal; Gupta, Atul; Ramesh, M. Lakshmi; Reddy, P. Vedamurthy; Yuvaraju, Y.; Yaswanth, G. (International Journal of Research in Medical Sciences, 2025)
Background: In urological practice, urethral stricture disease is a prevalent condition. In comparison to the other sites, the bulbar urethral stricture imposes a greater load. The buccal mucosal graft (BMG) has been considered an optimal kind of urethral replacement since 1941. A lifetime success rate of 92% is achieved with standard bulbar urethroplasty employing BMG. There exist several methodologies for BMG urethroplasty, namely dorsal, ventral, and lateral approaches, which depend on the discretion of the surgeon. Methods: An observational study was done among 40 patients, divided into two groups each based on the procedure done. Age more than 18 years who are fit for the procedure, stricture length more than 2 cm on retrograde urethrogram (RGU) and patients who were willing to give informed consent were included in the study. Post operatively, all the patients were assessed at every 3-month interval up-to 18 months. The outcome parameters noticed were post voidal residual (PVR), Qmax, international prostate symptom score (IPSS) score. Results: There was no difference between the pre-operative and post-operative Qmax, PVR, IPSS score between the study groups. Conclusions: The findings of the present study concluded that there is no difference between dorsal and ventral onlay BMG urethroplasty in terms of increase in Qmax and decrease in PVR at the end of study period.